1994
DOI: 10.1136/oem.51.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos, cement, and cancer in the right part of the colon.

Abstract: Objective-The aim was to investigate associations between exposure to mineral fibres and dust, and cancer in subsites within the large bowel. Design-Pooled retrospective cohort studies. Subjects and settings-Blue collar workers, employed for at least one year in different trades; asbestos cement or cement workers (n = 2507), other industrial workers (n = 3965), and fishermen (n = 8092). Main outcome measures-Standardised incidence ratios (SIRs, national reference rates) were calculated for cause specific cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 39 publications
2
12
1
Order By: Relevance
“…In our study no association with duration of employment, time since first employment, or period of first employment was found for colorectal cancer. A predominance of rectal cancer was found, in contrast to the findings of Jakobsson et al (33), among Swedish asbestos-cement workers.…”
Section: Other Types Of Cancercontrasting
confidence: 56%
“…In our study no association with duration of employment, time since first employment, or period of first employment was found for colorectal cancer. A predominance of rectal cancer was found, in contrast to the findings of Jakobsson et al (33), among Swedish asbestos-cement workers.…”
Section: Other Types Of Cancercontrasting
confidence: 56%
“…Albin and coworkers found that colorectal cancer risks increased with cumulative exposure to mainly chrysotile asbestos [Albin et al, 1990]. Jakobsson and colleagues [Jakobsson et al, , 1994 found a 50% increased rate of the incidence of colorectal cancer among Swedish asbestos cement workers. A case-control study conducted in Stockholm (1986±1989) [de Gerhardsson et al, 1992] showed a 90% excess risk of both colon and rectum cancers in men who reported exposure to asbestos.…”
Section: Occupational Agentsmentioning
confidence: 98%
“…The asbestos-associated risk of malignancies other than lung cancer and mesothelioma is less established. However, there are several reports of an elevated risk of laryngeal cancer (2)(3)(4), and some studies have also found an increased risk of cancer of the kidney and gastrointestinal tract (5,6). Estimates of the current annual cancer burden due to past asbestos exposure in Finland range from 150 to more than 250 (7,8).…”
mentioning
confidence: 99%